Perbaikan Postur Kerja Karyawan di UMKM Hilwafa Menggunakan Metode REBA dengan Tools Nordic Body Map - Sibarani, Perpetua Glenn; Wijayanto, Dedi; Batubara, Hafzoh (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
UMKM Hilwafa is a business engaged in chip production. The frying process is carried out manually and poses a risk of musculoskeletal disorders (MSDs) due to non-ergonomic working postures. This study aims to analyze and improve workers’ postures using the Rapid Entire Body Assessment (REBA) method with the Nordic Body Map (NBM) tool, as well as to design an assistive device to reduce injury risk. Data were collected through direct observation, NBM questionnaires, and body dimension measurements. Initial analysis showed an NBM score of 77.75 (high risk) and a REBA score of 12 (immediate action required). Based on anthropometric data, an ergonomic work table was designed and implemented in the frying process. After improvement, the NBM score decreased to 57 and the REBA score to 5, indicating a significant reduction in risk. The findings demonstrate that the assistive device effectively reduces MSDs and enhances comfort and work efficiency.